2019
DOI: 10.1002/apj.2304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of hydrodesulfurization of coal tar using Pd/ZSM‐5/γ‐Al2O3 catalyst

Abstract: In this study, all‐atom model of Pd/ZSM‐5/γ‐Al2O3 was developed and validated by comparing the experimental results of nitrogen adsorption isotherm, pore structure parameters, and powder X‐ray diffraction to our simulation results. Coal tar was simulated using dibenzothiophene (DBT), and tetralin (THN) in our study, and the product of coal tar hydrodesulfurization was modeled by H2S and n‐hexane (Hex). The adsorption and diffusion of the DBT, THN, and Hex on Pd/ZSM‐5/γ‐Al2O3 were investigated, and the simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The FC zeolite shortens the diffusion path and reduces diffusion resistance for the methanol, alkanes, and aromatic hydrocarbons to rapidly diffuses to the catalyst surface by the mesoporous. However, the single microporous structure has a negative impact on the ZSM-5 catalytic process due to its extremely narrow and elongated micro-channel arrangement which limits mass transfer and facilitated coke formation (Groen et al, 2010; Chu et al, 2019). The introduction of TiO 2 coating greatly promotes the formation of a dense and uniform b-oriented ZSM-5 zeolite film.…”
Section: Resultsmentioning
confidence: 99%
“…The FC zeolite shortens the diffusion path and reduces diffusion resistance for the methanol, alkanes, and aromatic hydrocarbons to rapidly diffuses to the catalyst surface by the mesoporous. However, the single microporous structure has a negative impact on the ZSM-5 catalytic process due to its extremely narrow and elongated micro-channel arrangement which limits mass transfer and facilitated coke formation (Groen et al, 2010; Chu et al, 2019). The introduction of TiO 2 coating greatly promotes the formation of a dense and uniform b-oriented ZSM-5 zeolite film.…”
Section: Resultsmentioning
confidence: 99%
“…The FC zeolite shortens the diffusion path and reduces diffusion resistance for the methanol, alkanes, and aromatic hydrocarbons to rapidly diffuses to the catalyst surface by the mesoporous. However, the single microporous structure has a negative impact on the ZSM-5 catalytic process due to its extremely narrow and elongated microchannel arrangement which limits mass transfer and facilitated coke formation (Groen et al, 2010;Chu et al, 2019). The introduction of TiO 2 coating greatly promotes the formation of a dense and uniform b-oriented ZSM-5 zeolite film.…”
Section: Catalytic Performancementioning
confidence: 99%
“…There have been other several studies on PIM-1/UiO-66 MMM (Khdhayyer et al, 2017;Tien-Binh et al, 2018;Yu et al, 2019), however their scope was limited to membranes for gas separation applications. Several other studies have also reported on other types of MOF/Carbon composites such as MOF-5/expanded natural graphite (ENG) , MIL-101(Cr)/ZTC (Musyoka et al, 2016) and HKUST-1/graphene platelets (Hassan et al, 2019) (Marti et al, 2018) have been reported.…”
Section: Supplementary Materialsmentioning
confidence: 99%